Laparoscopic Treatment of Hydrocele of the Canal of Nuck in Pediatric Patients - Lee, Sung Ryul (European Journal of Pediatric Surgery, 2018)
Introduction Hydrocele of the canal of Nuck (HCN) causes an inguinal swelling in pediatric females similar to that observed in case of inguinal hernia. HCN should be considered in the differential diagnosis of hernia in such children. Although laparoscopic operations have been reported in several cases for the treatment of HCN in adults, they have not been reported for the treatment in pediatrics. This study aimed to evaluate the outcomes of laparoscopic intracorporeal hydrocelectomy with high ligation as a treatment for HCN in pediatrics.Materials and Methods I retrospectively reviewed the charts of 26 pediatric females aged ≤10 years who underwent laparoscopic hydrocelectomy with high ligation at Damsoyu Hospital, Seoul, Republic of Korea from September 2012 to December 2016.Results The mean age was 3.31 (1–10) years. HCN was on the right in 11 patients and on the left in 15. The presenting symptom in all cases was inguinal swelling. HCN was of the hourglass type inside the inguinal canal in 17 patients and in the abdominal cavity outside the inguinal canal in 9. All patients were treated with laparoscopic hydrocelectomy with high ligation. The mean operating time was 17.8 minute (15–30). The wounds were scarcely visible immediately after surgery. There were no postoperative complications and no recurrences on follow-up.Conclusion Laparoscopic intracorporeal hydrocelectomy with high ligation is effective for HCN in pediatrics owing to its short operating time, excellent cosmesis, and no recurrence.
Keywords: hydrocele of the canal of Nuck; laparoscopic hydrocelectomy; pediatric female